Hubungan Durasi Hipertensi dengan Tingkat Kecemasan pada Lansia - Purnama Neno, Ria; Vonny Lasanuddin, Hamna; Ariane Gobel, Inne (Pustaka Galeri Mandiri, 2026)
Hypertension is one of the most common chronic diseases experienced by the elderly and may cause psychological problems such as anxiety. The longer elderly individuals suffer from hypertension, the greater the risk of experiencing anxiety due to concerns about disease complications, long-term treatment, and physical limitations. This study aimed to determine the relationship between the duration of hypertension and anxiety levels among elderly people in Pentadio Timur Village, Telaga Biru District, Gorontalo Regency. This study used a quantitative method with an analytic observational design and a cross-sectional approach. The sample consisted of 68 respondents selected using purposive sampling technique. Data were collected using an observation sheet regarding the duration of hypertension and the Zung Self-Rating Anxiety Scale (ZSAS) questionnaire. Data analysis was conducted using the Chi-Square test with a significance level of ? = 0.05. The results showed that most respondents had suffered from hypertension for more than 10 years (38.2%) and experienced mild anxiety (55.9%). The Chi-Square test showed a p-value of 0.000 (p < 0.05), indicating a significant relationship between the duration of hypertension and anxiety levels among the elderly. The longer the elderly experienced hypertension, the higher the anxiety level tended to be. Therefore, psychological assessment and holistic nursing interventions are needed to improve the quality of life of elderly patients with hypertension